2015
DOI: 10.1186/s12863-015-0198-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the genetic variability amongst mandarin (Citrus reticulata Blanco) accessions in Bhutan using AFLP markers

Abstract: BackgroundBhutan is a small Himalayan country lying within the region considered to be the origin of citrus. Diverse citrus wild types grow naturally in different climates, elevations and edaphic conditions, but only mandarin is cultivated commercially. The first report of Huanglongbing (also known as greening disease) in Bhutan in 2003, and the threat it posed to the country’s citrus orchards prompted the collection of mandarin germplasm from across the country. This paper describes the genetic diversity of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 34 publications
(24 reference statements)
1
18
0
Order By: Relevance
“…The highest flower pedicel length 0.33 and 0.35 cm observed with the new strain while the lowest length of flower pedicel 0.247 and 0.270 cm obtained with local Mexican lime in both seasons. Also, the highest stamen number obtained by new strain lime which ranges from 22.0 to 21.75 compared with local Mexican lime which ranges from 18.5 to19.5 .The abovementioned results are in agreement with the results obtained by El-Barkouky and Khalil (1993) on lime, Dorji and Yapwattanaphun (2011). and Kinley and Chinawat (2011)on mandarin trees.…”
Section: Flower Characterssupporting
confidence: 88%
“…The highest flower pedicel length 0.33 and 0.35 cm observed with the new strain while the lowest length of flower pedicel 0.247 and 0.270 cm obtained with local Mexican lime in both seasons. Also, the highest stamen number obtained by new strain lime which ranges from 22.0 to 21.75 compared with local Mexican lime which ranges from 18.5 to19.5 .The abovementioned results are in agreement with the results obtained by El-Barkouky and Khalil (1993) on lime, Dorji and Yapwattanaphun (2011). and Kinley and Chinawat (2011)on mandarin trees.…”
Section: Flower Characterssupporting
confidence: 88%
“…Previous studies have shown that populations with limited outcrossing tend to having a low level of genetic diversity and a moderate to high level of genetic differentiation (Al-Sadi et al 2012;Al-Maamari et al 2014;Gannibal et al 2014;Al-Sadi et al 2015). However, it has been reported that there was a range of polymorphism (41-70%) in mandarin analyzed by AFLP which suggested the possibility of having diverse type of mandarins within the accessions examined (Dorji & Yapwattanaphun 2015). Genetic variation and their relatedness studied in pummelo cultivars with AFLP markers indicated that the similarity was high in samples even collected from different locations.…”
Section: Discussionmentioning
confidence: 87%
“…The AFLP markers are described as a strong molecular apparatus extensively exercised in genetic mapping, population genetics, phylogenetics or plant cultivar documentation. The AFLP procedure is extremely steady and has the capacity of reproducibility without depending on earlier sequence information (Liang et al 2007;Al-Sadi et al 2012;Dorji & Yapwattanaphun 2015). It has been used in phylogenetic studies of citrus and related genera (Chao et al 2005;Althoff et al 2007;Pang et al 2007;Dorji & Yapwattanaphun 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(Palmer et al, 1988;Bayer et al, 2009;Lu et al, 2011). More recently, different molecular markers such as cleaved amplified polymorphic sequence (CAPS) of cpDNA (Yamamoto et al, 2013;Ninomiya et al, 2015;Fujii et al, 2016) (Nonaka et al, 2017;Dorji and Yapwattanaphun, 2015;Froelicher et al, 2011), have been used for identification, parentage analysis and phylogeny of citrus species or cultivars.…”
Section: Introduction Smentioning
confidence: 99%